A New Induction Motor Adaptive Robust Vector Control based on Backstepping - Mhamed Madark; A. Ba-Razzouk; E. Abdelmounim; M.El Malah (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper, a novel approach to nonlinear control of induction machine, recursive on-line estimation of rotor time constant and load torque are developed. The proposed strategy combines Integrated Backstepping and Indirect Field Oriented Controls. The proposed approach is used to design controllers for the rotor flux and speed, estimate the values of rotor time constant and load torque and track their changes on-line. An open loop estimator is used to estimate the rotor flux. Simulation results are presented which demonstrate the effectiveness of the control technique and on-line estimation.